SHARIAH GOVERNANCE OF CRYPTOCURRENCIES: Risks, Parameters and Regulatory Solutions - Balarabe, Abubakar; Abdullah, Md. Faruk; Rahman, Md. Habibur; Daud, Mohd Zaidi (Fakultas Syariah, 2025)
The introduction of cryptocurrencies into Islamic finance raises critical Shariah issues that require systematic evaluation through the lens of maqāṣid al-sharīʿah, specifically ḥifẓ al-māl (protection of wealth) and darʾ al-mafāsid (prevention of harm). This study conducts an empirical legal analysis by examining how risks and uncertainties prevent cryptocurrencies from functioning as Shariah-compliant money and analyses the conditions or regulations that could enable Shariah-compliant cryptocurrency transactions and develop Shariah parameters. Focusing on the Malaysian context, the study conducts qualitative interviews with 12 experts, including Shariah scholars, regulators, academics, and fintech practitioners. The methodology provides an in-depth examination of this multifaceted topic and seeks to bridge the gap between Shariah, finance, and new technologies. The findings highlight major concerns such as gharar (uncertainty), maysir (speculation), lack of intrinsic value, and potential involvement in unlawful activities. Additional challenges include decentralisation, lack of transparency, weak public awareness, and contradictory fatwas. To address these issues, the study proposes a multi-level framework including Shariah certification, stablecoin development, asset protection mechanisms, risk mitigation tools, and institutional collaboration between regulators, scholars, and fintech developers. These findings contribute to the discourse on adapting new technologies to Islamic finance while providing practical guidance for policy development in Malaysia’s dual financial system. Masuknya mata uang kripto ke dalam sistem keuangan Islam menimbulkan sejumlah persoalan syariah yang krusial dan memerlukan evaluasi sistematis melalui perspektif maqāṣid al-sharīʿah, khususnya ḥifẓ al-māl (perlindungan harta) dan darʾ al-mafāsid (pencegahan kemudaratan). Penelitian ini melakukan analisis hukum empiris dengan mengkaji bagaimana risiko dan ketidakpastian menghambat mata uang kripto untuk berfungsi sebagai alat tukar yang sesuai dengan prinsip syariah, serta menganalisis kondisi atau regulasi yang dapat memungkinkan transaksi mata uang kripto yang patuh syariah sekaligus merumuskan parameter syariah yang relevan. Dengan berfokus pada konteks Malaysia, penelitian ini melaksanakan wawancara kualitatif terhadap 12 orang ahli yang terdiri atas ulama syariah, regulator, akademisi, dan praktisi teknologi finansial (fintech). Metodologi ini memungkinkan kajian yang mendalam terhadap isu yang bersifat multidimensional serta berupaya menjembatani kesenjangan antara prinsip syariah, sistem keuangan, dan perkembangan teknologi baru. Temuan penelitian menyoroti berbagai persoalan utama, seperti gharar (ketidakpastian), maysir (spekulasi), ketiadaan nilai intrinsik, serta potensi keterlibatan dalam aktivitas yang tidak sah menurut hukum. Tantangan tambahan meliputi sifat desentralisasi, kurangnya transparansi, rendahnya tingkat literasi publik, serta adanya fatwa yang saling bertentangan. Untuk mengatasi permasalahan tersebut, penelitian ini mengusulkan suatu kerangka kerja bertingkat yang mencakup sertifikasi syariah, pengembangan stablecoin, mekanisme perlindungan aset, instrumen mitigasi risiko, serta kolaborasi kelembagaan antara regulator, ulama, dan pengembang fintech. Temuan ini berkontribusi pada pengembangan wacana adaptasi teknologi baru dalam keuangan Islam sekaligus memberikan panduan praktis bagi perumusan kebijakan dalam sistem keuangan ganda Malaysia.